Unusual combination of acute aortic dissection, Mayer-Rokitansky-Küster-Hauser syndrome, and 46,XX gonadal dysgenesis: A case report - Zeng, Yifan; Hu, Yerong; Jiang, Bo; Tan, Ling; Tang, Hao (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute Stanford type A aortic dissection (ATAAD) is a life-threatening disease. The elderly are the high-risk population for aortic dissection (AD). Young patients with AD usually have heritable connective tissue diseases such as Marfan syndrome and Loeys-Dietz syndrome. However, young AD patients without heritable connective tissue disease are relatively rare. Case presentation: Herein, we report a case of 25-year-old female diagnosed with ATAAD accompanied with undeveloped secondary sexual characteristics. Computed tomography angiography showed that her AD involved the ascending and abdominal aorta. She had undergone thoracic endovascular aortic stent graft implantation in a local hospital due to acute Stanford type B aortic dissection at age 19. No uterus or ovaries were found on computed tomography angiography and transabdominal ultrasonography. Sex hormone detection revealed a low estrogen level. G-banded karyotyping analyses revealed a normal 46,XX karyotype. Finally, her abnormalities in the reproductive system were diagnosed as MRKH syndrome and 46,XX gonadal dysgenesis. Whole exome sequencing in the patient found SNP variant of ACTA2 c.773G>A and MYH11 c.5081A>G. MYH11 c.5081A>G was also found in her mother and younger brother. Copy number variations sequencing found an approximately 109.30Kb duplication at chromosome 6p22.3 (Chr 6: g.24920238-25029535) with a copy number of 3. We performed emergent total aortic arch replacement with frozen elephant trunk surgery, and the patient recovered well after surgery. However, her abdominal AD was stilling progression during 6 months of follow-up. Conclusion: To our knowledge, we report the world's first case of early-onset recurrent aortic dissection combined with MRKH syndrome and 46, XX gonadal dysgenesis.